2022
DOI: 10.1021/acsnano.2c07691
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Single-Atom Iron Nanozymes with Radiation-Enhanced Self-Cascade Catalysis and Self-Supplied H2O2 for Radio-enzymatic Therapy

Abstract: Single-atom nanozymes (SAzymes), with individually isolated metal atom as active sites, have shown tremendous potential as enzyme-based drugs for enzymatic therapy. However, using SAzymes in tumor theranostics remains challenging because of deficient enzymatic activity and insufficient endogenous H2O2. We develop an external-field-enhanced catalysis by an atom-level engineered FeN4-centered nanozyme (FeN4-SAzyme) for radio-enzymatic therapy. This FeN4-SAzyme exhibits peroxidase-like activity capable of catalyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 87 publications
1
43
0
Order By: Relevance
“…The effect of temperature on the POD-like activity of Mn-SAzymes was measured by adding Mn-SAzymes (20 μL, 1 mg/mL) into the water to adjust the total volume to 2 mL, the TMB concentration to 1 mM, and the H 2 O 2 concentration to 1 M. The mixture was then incubated at a set temperature (10,20,30,40,50,60, 70 °C) for 5 min, and the absorbance at 652 nm of the mixture was detected with a UV− Vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of temperature on the POD-like activity of Mn-SAzymes was measured by adding Mn-SAzymes (20 μL, 1 mg/mL) into the water to adjust the total volume to 2 mL, the TMB concentration to 1 mM, and the H 2 O 2 concentration to 1 M. The mixture was then incubated at a set temperature (10,20,30,40,50,60, 70 °C) for 5 min, and the absorbance at 652 nm of the mixture was detected with a UV− Vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Since the emergence of single-atom nanozymes, numerous reports have been made on single-atom nanozymes. They mainly focus on sensing and detection and biomedicine, and there are relatively few studies on dye degradation. , Single-atom catalysts can greatly reduce the use of precious metals because of their high atomic utilization, which is a great help for cost control. In the field of nanozymes, there are more research studies on manganese oxides, but there are few studies on single-atom nanozymes with manganese as the metal center, mostly with the coordination structure of Mn and N, and the effects of other heteroatom doping on the activity of manganese-based nanozymes need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a cell-death pathway via the accumulation of lipid peroxides in an iron-dependent manner. , Diverse iron-based nanozymes have been reported to induce ferroptosis via oxidization of polyunsaturated fatty acids (PUFAs) and then lipid peroxidization (LPO). , However, the Fe-based nanozyme-induced ferroptosis stress is suboptimal owing to weak Fenton activities and the intrinsic high glutathione (GSH) level in the tumor microenvironment (TME). Additionally, glutathione peroxidase 4 (GPx-4) can effectively regulate ferroptosis, which uses GSH as a cofactor to reduce lipid peroxides . Previous studies demonstrated that depletion of GSH could inactivate GPx-4 and induce irreversible LPO. ,, SAEs have been extensively exploited and made profound progresses of ferroptosis-based tumor therapy. For instance, Chang et al prepared nitrogen (N)-doping carbon-supported Pd SAE with superior peroxidase (POD)-like and glutathione oxidase (GSHOx)-like catalytic performances, significantly boosting the intracellular oxidative stress, resulting in LPO-induced ferroptosis .…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies demonstrated that depletion of GSH could inactivate GPx-4 and induce irreversible LPO. 24,36,37 SAEs have been extensively exploited and made profound Pd SAE with superior peroxidase (POD)-like and glutathione oxidase (GSHOx)-like catalytic performances, significantly boosting the intracellular oxidative stress, resulting in LPOinduced ferroptosis. 18 Cao et al reported an engineered DNA modulator-based Fe SAE for ferroptosis-based cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the adjustable coordination environment and structure of ASCs make it feasible to obtain uniform catalytic active centers, making them an ideal bridge between homogeneous catalysts and heterogeneous catalysts. [27][28][29][30][31][32][33] For CO 2 R, the reaction often involves multiple proton-coupled electron transfer processes and complex intermediates, and the well-defined structure of ASCs will help us to understand the reaction mechanism, thereby guiding the design and development of advanced catalysts. At present, a variety of ASCs have been developed, such as atomically dispersed Fe, Co, Ni, etc.…”
Section: Introductionmentioning
confidence: 99%